The value of graduated compression socks as a post-exercise recovery modality in long distance runners - Welman, K. E. (University of Stellenbosch, 2011)
The purpose of this two part investigation was to examine the efficacy of graduated compressive knee-high socks (CS) to modulate the recovery of muscle damage and athletic performance in well trained distance runners after an actual 56 km ultra marathon. In the first part of the research (part I) the objective was to compare the use of graduated compression socks and a placebo sock during a 56 km ultra distance event. The next part of the investigation (part II) endeavoured to establish the optimal time to wear graduated compression socks i.e. during or after exercise. In part I, 40 competitive male distance runners (age: 42 . 8 years; VO2max: 50 . 8 mL.kg-1.min-1; height: 180 . 7 cm and body mass: 80 . 10 kg) were randomly divided into an experimental (EXP) and control (C) group. The EXP group wore compression socks (.20 . 30 mmHg) during the 56 km race as well as for the subsequent 72 hours, while the C group wore a placebo sock (.0 mmHg). In part II, 43 competitive male distance runners (age: 41 . 8 years; VO2max: 49 . 6 mL.kg-1.min-1; height: 178 . 6 cm and body mass: 76 . 11 kg) were randomly divided into three treatment groups CSRun, CSRec and CSRun&Rec. In both parts recovery was assessed by measuring serum creatine kinase (CK), skeletal myoglobin (s-Mgb), C -reactive protein (hsCRP), lower limb circumferences (cmf), blood lactate (LT), Visual analogue scales (VAS), running economy (RE) and a peak power (PP) for muscle function. All variables in both parts changed significantly over time, indicating that the 56 km did induce muscle damage (P < 0.05). The EXP group in part I demonstrated lower s-Mgb levels directly after the 56 km race (P < 0.05), reduced swelling in calf and ankle (P < 0.05) compared to the C group. CK, hsCRP and RE did not differ between the groups (P > 0.05). Runners perceived less pain in the calf and Quadriceps muscles until 48 hours subsequent to the race (P < 0.05). At 24 hours PP improved by 6.5% more in CS than C group. [La] was lower in those running with CS in both parts within 30 minutes after the race (P < 0.05). Part II corresponded to the results in part I with CSRun and CSRun&Rec demonstrating less s Mgb directly and at CK 24 and 48hrs compared to CSRec (P < 0.05). VAS, PP, RE and hsCRP did not differ between the three groups (P > 0.05). The results of part I suggest that wearing CS during a race and during a 72 hour recovery period has a beneficial effect on recovery time over the first 48 hours compared to those runners not wearing CS. Part II in this investigation suggest that wearing CS during exercise will reduce muscle damage more so than wearing the CS only subsequent to exercise.